2011
DOI: 10.1016/j.jenvman.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic treatment of sulfate-rich wastewater in an anaerobic sequential batch reactor (AnSBR) using butanol as the carbon source

Abstract: Biological sulfate reduction was studied in a laboratory-scale anaerobic sequential batch reactor (14 L) containing mineral coal for biomass attachment. The reactor was fed industrial wastewater with increasingly high sulfate concentrations to establish its application limits. Special attention was paid to the use of butanol in the sulfate reduction that originated from melamine resin production. This product was used as the main organic amendment to support the biological process. The reactor was operated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…With the in-depth research on SRB and the development of anaerobic reactors, researchers and engineers are increasingly interested in using some modern new high-efficiency anaerobic reactors to treat high-sulfate wastewater. [21][22][23][24][25][26][27][28][29][30][31] Modern anaerobic treatment systems depend to a certain extent on the formation of a stable and balanced micro-ecosystem.…”
Section: Biochemical Processmentioning
confidence: 99%
“…With the in-depth research on SRB and the development of anaerobic reactors, researchers and engineers are increasingly interested in using some modern new high-efficiency anaerobic reactors to treat high-sulfate wastewater. [21][22][23][24][25][26][27][28][29][30][31] Modern anaerobic treatment systems depend to a certain extent on the formation of a stable and balanced micro-ecosystem.…”
Section: Biochemical Processmentioning
confidence: 99%
“…The microbial community present in the inoculum needs to be assessed and optimized. Changes in the experimental conditions, such as to the influent sulfate concentration or COD/SO 4 2ratio, may lead to a better understanding of batch reactor operation for the treatment of sulfate-rich wastewater from industrial processes (Sarti et al, 2010;Sarti and Zaiat, 2011).…”
Section: Effect Of Metal Additionmentioning
confidence: 99%
“…It has been shown that the competition of SRB was more pronounced at low COD/SO 4 2− ratio in the wastewater (Singh et al 2014). The consumption of organic substrates in sulphate-laden wastewater is strongly dependent on the COD/SO 4 2− ratio (Sarti and Zaiat 2011). The COD/SO 4 2− ratio of 0.67 was reported to be theoretically optimum ratio for the significant removal of COD by SRB (Rinzema and Lettinga 1988).…”
Section: Introductionmentioning
confidence: 99%